1994
DOI: 10.1037/0022-006x.62.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy as a taxon: Evidence that psychopaths are a discrete class.

Abstract: Taxometric analyses were applied to the construct of psychopathy (as measured by the Psychopathy Checklist) and to several variables reflecting antisocial childhood, adult criminality, and criminal recidivism. Subjects were 653 serious offenders assessed or treated in a maximum-security institution. Results supported the existence of a taxon underlying psychopathy. Childhood problem behaviors provided convergent evidence for the existence of the taxon. Adult criminal history variables were continuously distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
364
7
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(387 citation statements)
references
References 29 publications
13
364
7
3
Order By: Relevance
“…The Child and Adolescent Taxon Scale (CATS; Harris, Rice, & Quinsey, 1994;Quinsey, Harris, Rice, & Cormier, 2006) is an actuarial rating scale developed from variables related to childhood and adolescent antisocial and aggressive characteristics (e.g., childhood aggression problem, arrested below the age of 16). This scale has eight items scored either 0 (No) or 1 (Yes).…”
Section: Methodsmentioning
confidence: 99%
“…The Child and Adolescent Taxon Scale (CATS; Harris, Rice, & Quinsey, 1994;Quinsey, Harris, Rice, & Cormier, 2006) is an actuarial rating scale developed from variables related to childhood and adolescent antisocial and aggressive characteristics (e.g., childhood aggression problem, arrested below the age of 16). This scale has eight items scored either 0 (No) or 1 (Yes).…”
Section: Methodsmentioning
confidence: 99%
“…15 The two groups did not differ in age, gender, ethnicity, handedness, or substance dependence. 12 This cutoff was chosen to be consistent with our previous research on this sample, 9,12,15 and is similar to the optimal cutoff suggested by taxometric analyses of the PCL-R. 16 Full informed, written consent was obtained from all subjects in accordance with Institutional Review Board procedures at University of Southern California. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The Childhood and Adolescent Taxon Scale self-report version (CAT-SR; Seto et al 1997) consists of eight items that measure early behavioral problems associated with adult psychopathy (Harris, Rice, and Quinsey 1994). Each of the eight items is scored as absent (0), some indication (1), or present (2), and an average of the eight items is taken.…”
Section: Methodsmentioning
confidence: 99%